Quick-scan estimating model of higher heating value of oil palm empty fruit bunches based on ash from proximate analysis data (2014)
A correlation model for a quick-scan estimation of the Higher Heating Value (HHV) of Oil Palm Empty Fruit Bunches (EFB) base on proximate analysis is presented in this paper. The proximate analysis variables Fixed Carbon (FC), Ash Content (Ash), Volatile Matter (VM), Residual Moisture were analyzed statistically to obtain a model to estimate HHV which can be used as a support for evaluating the energetic disponibility of the EFB,  with Ash content as the input variable.  The samples were taken directly from the end of the processing line (the process exit after the fruit removal section) in facilities of agro-industrial companies located in the Colombian coast. The average HHV obtained was 16.18 MJ/kg, and the minimum and maximum value of HHV was 13.6 MJ/kg and 19.51 MJ/kg, respectively.